The "Keynesian moment" in policymaking, the perils ahead, and a flow-of-funds interpretation of fiscal policy - Andrea Terzi (Levy Economics Institute of Bard College, 2010)
With the global crisis, the policy stance around the world has been shaken by massive government and central bank efforts to prevent the meltdown of markets, banks, and the economy. Fiscal packages, in varied sizes, have been adopted throughout the world after years of proclaimed fiscal containment. This change in policy regime, though dubbed the 'Keynesian moment,' is a 'short-run fix' that reflects temporary acceptance of fiscal deficits at a time of political emergency, and contrasts with John Maynard Keynes's long-run policy propositions. More important, it is doomed to be ineffective if the degree of tolerance of fiscal deficits is too low for full employment. Keynes's view that outside the gold standard fiscal policies face real, not financial, constraints is illustrated by means of a simple flow-of-funds model. This shows that government deficits do not take financial resources from the private sector, and that demand for net financial savings by the private sector can be met by a rising trade surplus at the cost of reduced consumption, or by a rising government deficit financed by the monopoly supply of central bank credit. Fiscal deficits can thus be considered functional to the objective of supplying the private sector with a provision of financial wealth sufficient to restore demand. By contrast, tax hikes and/or spending cuts aimed at reducing the public deficit lower the available savings of the private sector, and, if adopted too soon, will force the adjustment by way of a reduction of demand and standard of living. This notion, however, is not applicable to the euro area, where constraints have been deliberately created that limit public deficits and the supply of central bank credit, thus introducing national solvency risks. This is a crucial flaw in the institutional structure of Euroland, where monetary sovereignty has been removed from all existing fiscal authorities. Absent a reassessment of its design, the euro area is facing a deflationary tendency that may further erode the economic welfare of the region.
Keywords: E12; E42; E62; 330; government and the monetary system; fiscal policy; Keynes; Euro area; Finanzmarktkrise; Subprime-Hypothek; Geldpolitik; Finanzpolitik; Keynesianismus; EU-Staaten